The Game Analysis of Information Sharing for Supply Chain Enterprises in the Blockchain - Tang, Qian; Zhang, Zeng; Yuan, Zhonglei; Li, Zhen (Frontiers in Manufacturing Technology, 2022)
The problems of additional inventory costs and inaccurate demand estimation caused by information asymmetry has severely damaged the profits of all participants and restricted the overall development of the supply chain. New technologies and ideas are urgently needed to solve these problems. The blockchain technology is widely accepted as a disruptive technology and a powerful tool to resolve information asymmetry with its advantage in decentralization, transparency, traceability, confidentiality, immutability, etc. The introduction of blockchain into the information system will effectively promote supply chain collaboration by facilitating information sharing among enterprises at various nodes. The paper builds a consortium chain model suitable for supply chain information sharing, uses evolutionary game theory to analyze the strategy changes and influencing factors in the information sharing choices of supply chain participants, and finally verifies the correctness of the results through MATLAB simulation.